To vaccinate or not to vaccinate? This is the question! Delay the Booster, maybe you get a Bratwurscht! - Karl-Heinz Moritz; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2021)
A game-theoretic setting is used to illuminate the conflict between vaccination proponents and vaccination opponents. A central result is that vaccination proponents could in principle persuade vaccination opponents to vaccinate by means of subsidization. Such a subsidy could increase benefits for both groups. Deeper analysis provides numerous further insights regarding the stability of these results.
Keywords: 330; vaccination; corona; covid; game theory; moral hazard